Fretting–corrosion at the modular tapers interface: Inspection of standard ASTM F1875-98. (May 2018) - Bingley, Rachel; Martin, Alan; Manfredi, Olivia; Nejadhamzeeigilani, Mahdiyar; Oladokun, Abimbola; Beadling, Andrew Robert; Siddiqui, Sohail; Anderson, James; Thompson, Jonathan; Neville, Anne; Bryant, Michael
Interest in the degradation mechanisms at the modular tapers interfaces has been renewed due to increased reported cases of adverse reactions to metal debris and the appearance of wear and corrosion at the modular tapers interfaces at revision. Over the past two decades, a lot of research has been expended to understand the degradation mechanisms, with two primary implant loading procedures and orientations used consistently across the literature. ASTM F1875-98 is often used as a guide to understand and benchmark the tribocorrosion processes occurring within the modular tapers interface. This article presents a comparison of the two methods outlined in ASTM F1875-98 as well as a critique of the standard considering the current paradigm in pre-clinical assessment of modular tapers.